DNA methylation changes at TREM2 intron 1 and TREM2 mRNA expression in patients with Alzheimer's disease - Ozaki, Yuki; Yoshino, Yuta; Yamazaki, Kiyohiro; Sao, Tomoko; Mori, Yoko; Ochi, Shinichiro; Yoshida, Taku; Mori, Takaaki; Iga, Jun-ichi; Ueno, Shu-ichi (Journal of psychiatric research, 2017)
Recent genome-wide association studies revealed that Triggering receptor expressed on myeloid cells 2 (TREM2) was associated with Alzheimer's disease (AD) and other neurodegenerative diseases. We previously reported that TREM2 mRNA is highly expressed in leukocytes of AD patients compared to those in healthy controls. However, the mechanism of TREM2 expression change is still not known. In this study, we examined the involvement of the DNA methylation status of TREM2 in its high gene expression. Fifty AD subjects and age- and sex-matched control subjects were recruited (25 males, 25 females; 79.9 ± 5.27 and 79.4 ± 3.92 years old, respectively). TREM2 mRNA expression and the percentage of DNA methylation at four CpG sites in intron 1 of TREM2 were studied using their peripheral leukocytes. We confirmed that TREM2 mRNA expression in leukocytes was significantly higher in AD patients than in controls (p = 0.007). The percentage methylation at three CpG sites in TREM2 intron 1 was significantly lower in AD subjects than in control: CpG1, 9.4 ± 3.2 vs 11.9 ± 4.0 (p = 0.001); CpG2, 15.4 ± 4.9 vs 19.1 ± 4.8 (p = 0.001); CpG3, 20.8 ± 5.5 vs 25.5 ± 5.4 (p < 0.001); and the average percentage methylation of all CpG sites: 13.5 ± 3.7 vs 16.1 ± 3.8 (p = 0.002), respectively. In addition, there were significant negative correlations between TREM2 mRNA expression and the percentage DNA methylation of each of CpG sites (CpG1, r = −0.416, p < 0.001; CpG2, r = −0.510, p < 0.001; CpG3, r = −0.504, p < 0.001; CpG4, r = −0.356, p < 0.001). Lower DNA methylation at TREM2 intron 1 caused higher TREM2 mRNA expression in the leukocytes of AD subjects versus controls and may be a biomarker for AD.